PENERAPAN HUKUM BERNOULLI PADA KONSEP PERANCANGAN GALERI PESAWAT TERBANG DAN KANTOR SEWA DI KEMAYORAN - Febrianto, Willy Steven; Lianto, Fermanto (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2020)
Along with the times, the Kemayoran area changed its function to become an office area, so that the history of Kemayoran is increasingly eroded. However, we cannot refuse the current of the times, especially the Kemayoran area, which has the potential to become a Central Business District (CBD). After searching the data by conducting interviews and surveys in the Kemayoran area and reviewing the literature, the urban acupuncture theory is used to answer the phenomenon that occurs, namely an aircraft history gallery and the additional function of the rental office will be used as an educational tourist spot where people can see various collections of aircraft from the Dutch, Japanese and Indonesian colonial times, and to fulfill Kemayoran's function as a CBD area. This building has a design concept taken from Bernoulli's law which is the movement of air as it passes through the wings of an aircraft and has a theme of aerospace. This gallery and rental office will be supported by programs such as movie showrooms, libraries, airplane exhibition rooms with a scale of 1:1, and workshops. With this building, it is hoped that the history of Kemayoran can be widely known by all circles and become a means of education, especially for the younger generation. Keywords: Airplane; Bernoulli; Gallery; Rental Office; Urban AcupunctureABSTRAKSeiring perkembangan zaman, daerah Kemayoran berubah fungsi menjadi daerah perkantoran, sehingga sejarah Kemayoran semakin lama semakin tergerus. Namun, kita tidak dapat menolak arus perkembangan zaman, terlebih daerah Kemayoran yang memiliki potensi menjadi daerah Central Business District (CBD). Setelah melakukan pencarian data dengan melakukan wawancara dan survei di kawasan Kemayoran serta mengkaji literatur, maka digunakan teori urban acupuncture untuk menjawab fenomena yang terjadi, yaitu sebuah galeri sejarah pesawat terbang dan fungsi tambahan kantor sewa akan dijadikan sebuah tempat wisata edukasi dimana orang-orang dapat melihat berbagai koleksi pesawat dari zaman penjajahan Belanda, Jepang, dan saat Indonesia merdeka, serta untuk memenuhi fungsi Kemayoran sebagai daerah CBD. Bangunan ini memiliki konsep perancangan yang diambil dari hukum Bernoulli yakni pergerakan udara saat melewati sayap pesawat dan memiliki tema kedirgantaraan. Galeri dan kantor sewa ini akan didukung dengan progam seperti ruang pertunjukan film, perpustakaan, ruang eksibisi pesawat dengan skala 1:1, dan workshop. Dengan adanya bangunan ini, diharapkan sejarah Kemayoran dapat dikenal luas oleh semua kalangan dan menjadi sarana edukasi khususnya bagi generasi muda.